Periodic Medical Examination and Occupational Health in Target Attainment of Workers in Rivers State, Nigeria - Abu, O. P.; Josiah, Gift (European Journal of Applied Sciences, 2022)
Work organisation equipment, facilities, and working conditions have potential sources of hazard and it is expected that organisation, protect, the health of vulnerable workers through health policy implementation. This paper was part of a study which was begun in 2016. Its main thrust of was to examine how Occupational Health policy implementation affects employee performance in two organisations; an agro-allied chemical company and an enamelware factory in Rivers State, Nigeria. Two research hypotheses were formulated to examine the relationship between periodic medical examination and the level of target attainment among workers; and the regularity of occupational health inspection and the level of target attainment among workers; The interactionist paradigm, the exchange theory was adopted. The study design was a descriptive survey. The stratified sampling technique was used to proportionately select 279 respondents from both organisations. Primary data were sourced directly from respondents through self questionnaires. Chi-square (X2) statistic at degree of freedom = 2 and 0.05 significance level was applied to test the research hypotheses. The findings showed that periodic medical examination is associated with the level of target attainment among workers, regular occupational health inspection was also associated with the level of target attainment among Workers. The study recommended that organisations should be committed to consistent implementation of occupational health policy that would enhance their well-being and in turn in improve workers’ performance. Employers should ensure that occupational health policy implementation should be made an integral part of work process and activities. A department should be created in firms to consistently evaluate and deal with the planned programme for employee health. Organisations should prioritize employee well-being by investing in human and material resources necessary for the effective implementation of occupational health policy.